EDUKASI PEMAHAMAN DAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK SEKOLAH DASAR KOTA SERANG - Evi Afiati; Arga Satrio Prabowo; Alfiandy Warih Handoyo; Rahmawati; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract The Indonesian Teachers' Union Federation has mentioned that there were three major sins in education during 2022. These three major sins are bullying, sexual harassment, and intolerance. Sexual harassment continues to be a struggle for the Indonesian nation to this day. According to a press release from the National Commission on Violence Against Women (Komnas Perempuan) on the 2022 Annual Report (CATAHU), there were a total of 338,496 reported cases of sexual harassment in 2021. According to the CATAHU 2021 data from Komnas Perempuan, over the past 10 years (2010-2020), the incidence of sexual violence against women has seen a significant increase, starting with 105,103 cases in 2010 and reaching 299,911 cases in 2020, with an average annual increase of 19.6%. Community Service activities were conducted to provide education on understanding and preventing sexual violence to elementary school students in the city of Serang. The activities included providing educational materials, showing educational videos to students, and engaging in games related to preventing child violence, followed by explanations and discussions. The results of this activity are reflected in the pre-test and post-test scores, where the pre-test score was 75%, while the post-test score was 96%. This indicates an increase in knowledge after receiving education on child sexual violence. Based on observations, students understand child sexual violence and agree on which parts of their bodies can and cannot be touched by others. They are also encouraged to always be open with their biological mother, teachers, or trusted individuals regarding suspected sexual violence. Keywords: Violence, Sexual, Elementary School Children, Serang City. Abstrak Federasi Serikat Guru Indonesia menyebutkan bahwa terdapat tiga dosa besar pendidikan selama 2022. Tiga dosa besar tersebut, yakni: kasus perundungan (bulliying), pelecehan seksual (sexual harrasment), dan intoleransi. Pelecehan seksual masih menjadi pergumulan bangsa Indonesia hingga kini. Saat ini, menurut siaran pers Komnas Perempuan tentang Catatan Tahunan (CATAHU) 2022, tercatat sebanyak 338.496 kasus pelecehan seksual yang telah diadukan pada tahun 2021. Menurut data CATAHU 2021 Komnas Perempuan, dalam kurun 10 tahun terakhir (2010-2020), angka kekerasan seksual terhadap perempuan banyak mengalami peningkatan, mulai dari 105.103 kasus pada tahun 2010 hingga mencapai 299.911 kasus pada tahun 2020 atau rata-rata kenaikan 19,6% per tahunnya. Kegiatan Pengabdian Masyarakat yang dilakukan adalah memberikan edukasi pemahaman dan pencegahan kekerasan seksual pada siswa Sekolah dasar Kota Serang. Kegiatan dilaksanakan melalui pemberian materi, para siswa diberikan tayangan tentang video edukasi dan permainan terkait pencegahan kekerasan anak, dilanjutkan dengan penjelasan dan diskusi. Hasil dari kegiatan ini dapat tergambar berdasarkan hasil pre-test dan post test, dimana hasil pre-test dengan nilai 75%, sedangkan hasil post-test didapatkan 96%, terdapat penambahan pengetahuan setelah diberikan edukasi tentang kekerasan seksual pada anak. Berdasarkan hasil pengamatan, siswa memahami kekerasan seksual pada anak dan menyepakati bagian tubuh yang boleh dan tidak boleh disentuh orang lain dan juga selalu untuk diajarkan selalu terbuka kepada Ibu kandung, guru atau kepada orang yang dipercaya terkait praduga kekerasan seksual Kata kunci : Kekerasan, Seksual, Anak Sekolah Dasar, Kota Serang.